The physiological origins of heart sounds and murmurs : the unique interactive guide to cardiac diagnosis - Criley, John Michael; Criley, David; Zalace, Conrad (Brown and Company, Boston : Little, 1995)
The multimedia CD-ROM integrate actual heart sounds with dynamic images, featuring : 135 clinical and diagnostic tutorials from the case files of a major teaching hospital, 200 actual heart saounds integrated with graphic images and more.
CD is available at Koleksi Media, Perpustakaan Perubatan and Perpustakaan HUKM
Syste, reguirement : macintosh : LC III or better, system 7.0 or later, 8 MB of RAM, 256 color monitor set at 640 480 pixels, dual speed CD-ROM drive
System requirements : windows ; 486SX processor or better, windows 3.1 or later, 8MB of RAM, 256 color super VGA monitor set at 640 480 pixels, dual speed CD-ROM drive or better, windows compatible sound card (16 bit sound card recommended), mouse and keyboard, external speakers, headphones, or a stethophone, a level II mutimedia PC is recommended.
English/Spanish
Keywords: Heart sounds -- physiology; Heart murmurs -- diagnosis